NEW APPROACHES TO THE ASSESSMENT OF THE QUALITY OF FAMILIES’ LIFE (review of the monograph "Social Work with Families Raising Children with Autism: A Strengths Development Intervention") - Polishchuk, Vira (Social work and education, 2023)
-